KEJAHATAN PERDAGANGAN ORANG (HUMAN TRAFFICKING) DI KABUPATEN SANGGAU DILIHAT DARI TINJAUAN VICTIMOLOGIS - NIM. A1012171039, MUHAMMAD FIKRI MUSTAQIM (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac The Trafficking in person is anextraordinary from of crime because it violates human rights. Sanggau regency is one of the regencies in the provinces of West Kalimantan which is derectly adjacent to Malaysia. Many people travel to Malaysia via cross-border mail at Entikong. The criminal art of trafficking in person in Sanggau district occured not only purely by the perpetrator but also by the role of the victim.The formulation of the problem in this study is